High-entropy sulfide modified electrode material and preparation method and application thereof

By growing CuInS2 nanosheet arrays on the surface of the copper sheet electrode and loading high entropy sulfide CFNWCS using the SILAR method to form the CFNWCS@CIS@CP electrode material, the problems of strict preparation conditions for high entropy sulfide and high cost of platinum-based electrodes are solved. It realizes efficient and low-cost hydrogen evolution performance of electrolytic water.

CN119121305APending Publication Date: 2024-12-13NANYANG NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411257699.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The preparation of existing high-entropy sulfide materials requires strict high-temperature and high-pressure conditions, which limits its large-scale application in electrolytic water electrode materials. Moreover, platinum-based electrodes are limited due to their scarcity and high cost, and lack low-cost and efficient Alternative materials.

Method used

The CuInS2 nanosheet array was grown in situ on the surface of the copper sheet electrode by hot solution vulcanization, and the high entropy sulfide CFNWCS was loaded on the surface of the CuInS2 electrode by continuous ion layer adsorption reaction method (SILAR), forming the CFNWCS@CIS@CP electrode material.

Benefits of technology

It realizes excellent photo-assisted electrolytic hydrogen evolution reaction activity and stability under full-spectrum simulated sunlight, significantly improves the electrolytic performance, and reduces the production cost and preparation complexity of electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121305A_ABST
    Figure CN119121305A_ABST
Patent Text Reader

Abstract

The invention provides a high-entropy sulfide modified electrode material and a preparation method and application thereof.The preparation method comprises the steps that firstly, a CuInS2 (CIS) nanosheet array grows on the surface of a copper sheet (CP) electrode in situ through a hot solution vulcanization method, and the CuInS2 nanosheet array serves as a photoactive substrate electrode to load high-entropy sulfide (CFNWCS) on the surface of the CIS electrode through a continuous ion layer adsorption reaction (SILAR); the prepared CFNWCS (at) CIS (at) CP electrode material as a water electrolysis catalyst shows excellent photo-assisted water electrolysis hydrogen evolution reaction (HER) activity and stability under full-spectrum simulated sun illumination, and compared with a CIS electrode and a non-high-entropy sulfide modified CIS electrode, the performance of photo-assisted water electrolysis is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrocatalytic materials for water electrolysis, in particular to a high-entropy sulfide modified electrode material and a preparation method and application thereof. Background Art

[0002] Water electrolysis technology is one of the effective ways to achieve my country's "dual carbon" goals. It can use green power sources such as solar cells to electrolyze water into clean and renewable hydrogen, providing solutions to alleviate energy shortages and environmental problems caused by fossil fuels in the future. The key to the water electrolysis reaction lies in the electrode material, so the development of efficient, durable and low-cost water electrolysis electrode materials is an important topic worthy of in-depth research.

[0003] At present, platinum-based electrodes are the most effective commercial water electrolysis electrode materials due to their excellent electrocatalytic performance. However, due to the scarcity and high cost of platinum metal, its long-term application is limited. A large number of studies have shown that metal sulfide catalysts are becoming potential materials to replace platinum-based electrodes due to their good conductivity and high activity. At the same time, emerging high-entropy alloy materials have also shown superior performance to traditional electrode materials in the field of water electrolysis, which is mainly due to the inherent "high entropy" properties of high-entropy alloys, such as high entropy effect, lattice distortion, slow diffusion and alloying effect, etc. These properties improve the activity and stability of water electrolysis from both thermodynamic and kinetic aspects. High-entropy alloy catalysts are mostly transition metal alloys, and the high-entropy sulfides, oxides and other compounds derived from them also have "high entropy" characteristics. Introducing the concept of "high entropy" into the design of metal sulfides is expected to break through the bottleneck of existing metal sulfide water electrolysis electrode materials and add a new paradigm to the high-entropy material system.

[0004] However, the preparation of high-entropy sulfides usually requires harsh high-temperature and high-pressure conditions, such as high-temperature element annealing, high-temperature thermal cracking, high-energy ball milling, etc., which greatly limits its practical application. Therefore, it is urgent to develop a new method for preparing high-entropy sulfides that is simple, fast, and low-temperature controllable, so as to lay the foundation for the large-scale application of high-entropy sulfide water electrolysis electrode materials. Summary of the invention

[0005] In order to solve the deficiencies in the prior art, the present invention provides a high entropy sulfide modified electrode material and its preparation method and application. The present invention first adopts a hot solution sulfidation method to in situ grow CuInS2 (CIS) nanosheet array on the surface of a copper sheet (CP) electrode, and uses this as a photoactive substrate electrode to load high entropy sulfide (CFNWCS) on the surface of the CIS electrode by means of a continuous ion layer adsorption reaction method (SILAR). The prepared CFNWCS@CIS@CP electrode material, as a water electrolysis catalyst, exhibits excellent light-assisted water electrolysis hydrogen evolution reaction (HER) activity and stability under full-spectrum simulated solar illumination, and significantly improves the performance of light-assisted water electrolysis compared to CIS electrodes and non-high entropy sulfide modified CIS electrodes.

[0006] In order to achieve the above object, the specific scheme adopted by the present invention is: The present invention discloses a method for preparing a high entropy sulfide modified electrode material, which mainly comprises the following steps: S1, pre-treating the copper sheet; S2. Preparation of CIS@CP Electrode S21, dissolving anhydrous indium chloride and thioacetamide in the first solvent, adding glacial acetic acid, and continuously stirring to obtain a colorless and transparent solution A; S22, vertically immersing the copper sheet pretreated in step S1 into solution A and reacting at 80°C, after the reaction is completed, rinsing the copper sheet with deionized water and drying at room temperature, i.e., in situ growing a CuInS2 nanosheet array on the surface of the copper sheet to obtain a CIS@CP electrode; S3. Preparation of high entropy sulfide modified electrode materials using SILAR method S31, containing Co 2+ , W 6+ 、Ni 2+ , Fe 3+ , Cu 2+ The metal salt of the ion is dissolved in the second solvent as a cation source to obtain a solution B, and the sulfide is dissolved in the second solvent to obtain a solution containing S 2- ion solution C, and two portions of the second solvent are recorded as solution D and solution E; S32, placing the CIS@CP electrode obtained in step S2 in solution B, solution D, solution C and solution E in order and soaking each for 20 seconds, completing one soaking process; S33. Repeat step S32 several times, then wash, and then dry at 100°C for 2 hours, that is, CFNWCS nanoparticles are loaded on the CIS@CP electrode to obtain a high-entropy sulfide-modified electrode material, which is recorded as CFNWCS@CIS@CP electrode material.

[0007] Furthermore, in step S1, the method for pretreating the copper sheet is: using 400 mesh, 1000 mesh and 2000 mesh metallographic sandpaper to polish the surface of the copper sheet until it is smooth, then washing it, drying it at room temperature and storing it in anhydrous ethanol for later use.

[0008] Furthermore, in step S21, the first solvent is deionized water; and in step S31, the second solvent is ethanol.

[0009] Furthermore, in step S21, the concentration of anhydrous indium chloride is 0.06M, and the concentration of thioacetamide is 0.12M.

[0010] Furthermore, in step S21, the amount of glacial acetic acid added per milliliter of the first solvent is 12 μL.

[0011] Further, in step S31, Co 2+ , W 6+ 、Ni 2+ , Fe 3+ , Cu 2+ The metal salts of ions are cobalt nitrate, tungsten hexachloride, nickel nitrate, iron nitrate, and copper nitrate; the sulfide is Na2S.

[0012] Further, in step S31, each ion in the cation source of solution B has an equal molar concentration; The total molar concentration of the cation source in solution B is proportional to the S in solution C. 2- The molar concentration of the ions is equal, both are 50 mM.

[0013] Furthermore, in step S33, step S32 is repeated 5 to 20 times.

[0014] On the other hand, the present invention discloses a high entropy sulfide modified electrode material, which is prepared by the above method.

[0015] On the other hand, the present invention discloses the application of high entropy sulfide electrode materials in the field of hydrogen production by water electrolysis.

[0016] Beneficial effects:

[0017] The present invention uses CIS as a photoactive component, which can effectively absorb the full spectrum of simulated sunlight, excite and generate photogenerated charge carriers. On the surface of the CIS@CP electrode, a highly efficient HER electrocatalyst, CFNWCS nanoparticles, is loaded. In the composite electrode system, first, the high-entropy sulfide nanoparticles provide more abundant HER active sites, thereby accelerating the kinetics of the hydrogen evolution reaction on the CIS surface. Secondly, the additionally excited high-energy photogenerated carriers can participate in the HER electrocatalytic reaction, further generating more HER active sites, which is manifested as a decrease in the light-assisted HER overpotential. In addition, the heterogeneous interface formed between CIS and CFNWCS high-entropy sulfide contributes to the effective separation of photogenerated electron-hole pairs, and accelerates the rapid transfer of electrons between the electrode-solution interface, promoting more electrons to participate in the HER process. In the system of ethylene glycol oxidation half reaction (EOR) coupled with HER half reaction, the composite electrode shows better light-assisted electrocatalytic performance than pure CIS electrode or non-high-entropy sulfide loaded electrode. The present invention adopts the room temperature SILAR method to prepare high-entropy sulfide, realizing a simple, fast, energy-saving and direct synthesis of high-entropy compounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 (a) is a schematic diagram of the preparation process of the CFNWCS@CIS@CP electrode in Example 1. Figure 1 (bd) are FE-SEM images of different samples, (b) the copper sheet after pretreatment in Comparative Example 1, (c) the CIS@CP electrode prepared in Comparative Example 2, the inset is a local enlarged view, (d) the CFNWCS@CIS@CP electrode prepared in Example 1, the inset is a local enlarged view, Figure 1 (el) is Figure 1 (d) EDX mapping of the inset.

[0019] Figure 2 XRD patterns of different electrodes prepared in Comparative Example 2 and Example 1: (a) is a spectrum with 2θ ranging from 10 to 80°, and (b) is an enlarged spectrum with 2θ ranging from 22.5 to 42.5° and 52 to 65°.

[0020] Figure 3 XPS graphs of different electrodes prepared in Comparative Example 2 and Example 1.

[0021] Figure 4 LSV diagrams of light-assisted electrocatalytic EOR coupled to HER prepared in Comparative Examples 1-6 and Example 1: (a) dark state, (b) illumination, and current density of -10 mA / cm in dark state and illumination 2 HER overpotential (c).

[0022] Figure 5Different electrochemical test results of the electrode prepared in Example 1 in the light-assisted electrocatalytic EOR coupled HER reaction system: (a) multiple current step method test, (b) constant potential (-0.4V vs. NHE) it test, the inset is the FE-SEM image of the sample after 60 minutes of test, (c) XRD pattern of the sample after 60 minutes of constant potential it test, (d) comparison of theoretical H2 production and actual H2 production during the constant potential it test and HER Faraday efficiency (FE).

[0023] Figure 6 for Figure 5 XPS graph of the electrode prepared in Example 1 after constant potential IT testing.

[0024] Figure 7 (a) is the diffuse reflectance spectrum (DRS) diagram of different electrodes prepared in Example 1 and Comparative Examples 2-6, (b) is the EIS diagram of different electrodes prepared in Example 1 and Comparative Examples 1-2, and the sample in Example 1 was tested in the dark state (-D) and under light (-L), respectively.

[0025] Figure 8 (ac) are dark state cyclic voltammetry (CV) test result diagrams of different electrodes prepared in Example 1 and Comparative Examples 1-2, and (d) is a CV test result diagram of the sample of Example 1 under light illumination, and the test potential range is the non-Faraday potential range.

[0026] Fig. 9 Reason Figure 8 The ECSA results of different electrodes were obtained by conversion. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] The invention discloses a high entropy sulfide modified electrode material and a preparation method and application thereof. The electrode material is a CIS nanosheet array@copper sheet electrode modified with high entropy sulfide CFNWCS nanoparticles, which can be abbreviated as CFNWCS@CIS@CP electrode material.

[0029] The preparation method of the high entropy sulfide modified electrode material mainly comprises the following steps: S1. Pre-treatment of copper sheet Use 400 mesh, 1000 mesh and 2000 mesh metallographic sandpaper to polish the copper sheet surface until it is smooth and no obvious lines can be observed with the naked eye. Then, ultrasonically clean it in deionized water, anhydrous ethanol and 3.0M hydrochloric acid solution for 10 minutes to remove dust, water-soluble and fat-soluble substances and oxide layer on the copper sheet surface. After completion, rinse it carefully with deionized water, dry it at room temperature and store it in anhydrous ethanol for later use; Preparation of S2 and CIS@CP electrodes S21, dissolving anhydrous indium chloride and thioacetamide in deionized water, wherein the concentration of anhydrous indium chloride is 0.06 M, and the concentration of thioacetamide is 0.12 M, and adding glacial acetic acid, and continuously stirring until a colorless and transparent solution A is formed; S22, immersing the copper sheet pretreated in step S1 vertically into solution A and reacting at 80°C for 30 minutes, washing the copper sheet with deionized water after the reaction is completed, and drying at room temperature to obtain a CIS@CP electrode; Preparation of S3 and CFNWCS@CIS@CP electrodes The high entropy sulfide CFNWCS nanoparticles were loaded on the CIS@CP electrode obtained in step S2 using the SILAR method, specifically: S31, containing Co 2+ , W 6+ 、Ni 2+ , Fe 3+ , Cu 2+ The metal salt of the ion is dissolved in the ethanol solvent as the cation source, and the cation source is ensured to be of equal substance concentration. The resulting solution is marked as solution B. At the same time, the solution obtained by dissolving the sulfide in the ethanol solvent is marked as solution S. 2- The source of ions is labeled as solution C, where the molar concentration of the cation source in solution B is equal to the molar concentration of S in solution C. 2- The concentration of anionic substances is equal; two portions of ethanol solvent are taken as solution D and solution E; S32, placing the CIS@CP electrode obtained in step S2 in solution B, solution D, solution C and solution E in order and soaking each for 20 seconds, completing one soaking process; S33. Repeat step S32 for 5 to 20 times. The obtained electrode sample is rinsed with deionized water and dried at 100° C. for 2 hours to obtain the CFNWCS@CIS@CP electrode material.

[0030] Preferably, in step S21, the amount of glacial acetic acid added per milliliter of solution is 12 μL.

[0031] Preferably, in step S31, Co 2+ , W 6+ 、Ni 2+ , Fe3+ , Cu 2+ The cationic metal salts are cobalt nitrate, tungsten hexachloride, nickel nitrate, iron nitrate and copper nitrate.

[0032] Preferably, the total molar concentration of the mixed cationic solution in step S31 is 50 mM.

[0033] Preferably, in step S31, 2- The solute of the ionic solution is Na2S, the solvent is ethanol, and the molar concentration is 50mM.

[0034] The technical solution of the present invention is described in detail below in conjunction with specific embodiments. It should be noted that the raw materials used in the present invention are all commercially available raw materials.

[0035] Example 1

[0036] A method for preparing a high entropy sulfide modified electrode material, such as Figure 1 (a), mainly including the following steps: S1. Copper sheet pretreatment The copper sheet was polished with 400-mesh, 1000-mesh and 2000-mesh metallographic sandpaper until it was smooth and no obvious lines could be observed with the naked eye. It was then ultrasonically cleaned in deionized water, anhydrous ethanol and 3.0M hydrochloric acid solution for 10 minutes to remove dust, water-soluble substances, fat-soluble substances and oxide layers on the surface of the copper sheet. After pretreatment, it was carefully rinsed with deionized water, dried at room temperature and stored in anhydrous ethanol for later use; Preparation of S2 and CIS@CP electrodes Anhydrous indium chloride and thioacetamide were dissolved in 40 mL of deionized water, wherein the concentration of anhydrous indium chloride was 0.06 M and the concentration of thioacetamide was 0.12 M, and 480 μL of glacial acetic acid was added and stirred continuously until a colorless and transparent solution A was formed. Subsequently, the vertical part of the copper sheet pretreated in step S1 was immersed in the above solution and reacted at 80°C for 30 min. After the reaction was completed, the copper sheet was rinsed with deionized water and dried at room temperature to obtain a CIS@CP electrode; Preparation of S3 and CFNWCS@CIS@CP electrodes The high entropy sulfide CFNWCS nanoparticles were loaded onto the CIS@CP electrode obtained in step S2 using the SILAR method, specifically: S31. Dissolve cobalt nitrate, nickel nitrate, iron nitrate, copper nitrate and tungsten hexachloride in ethanol as cation sources, and ensure that the mixed cation sources are of equal molar concentration. The resulting solution is marked as solution B. At the same time, dissolve Na2S in the same solvent as solution S. 2-The source of ions is marked as solution C, wherein the molar concentrations of cations and anions in solution B and solution C are equal to 50 mM; two portions of ethanol solvent are taken as solution D and solution E, and the continuous immersion solution system required for the SILAR method is formed by solution B, solution D, solution C and solution E; S32, placing the CIS@CP electrode obtained in step S2 in solution B, solution D, solution C and solution E in order and soaking each for 20 seconds, completing one soaking process; S33. Repeat step S32 10 times at room temperature; the obtained electrode sample is rinsed with deionized water and dried at 100°C for 2 hours to obtain CFNWCS@CIS@CP electrode material.

[0037] Example 2

[0038] The difference between Example 2 and Example 1 is that in step S33, step S32 is repeated 5 times at room temperature.

[0039] Example 3

[0040] The difference between Example 3 and Example 1 is that in step S33, step S32 is repeated 15 times at room temperature.

[0041] Example 4

[0042] The difference between Example 4 and Example 1 is that in step S33, step S32 is repeated 20 times at room temperature.

[0043] Comparative Example 1 (Copper Sheet (CP))

[0044] The difference between Comparative Example 1 and Example 1 is that it only includes step S1.

[0045] Comparative Example 2 (CIS@CP electrode)

[0046] The difference between Comparative Example 2 and Example 1 is that it only includes step S1 and step S2.

[0047] Comparative Example 3 (CS@CIS@CP)

[0048] The difference between Comparative Example 3 and Example 1 is that in step S31, the preparation method of solution B is: dissolving cobalt nitrate as a cation source in ethanol.

[0049] Comparative Example 4 (WCS@CIS@CP)

[0050] The difference between Comparative Example 4 and Example 1 is that in step S31, the preparation method of solution B is: dissolving cobalt nitrate and tungsten hexachloride as cation sources in ethanol, wherein the cobalt nitrate and tungsten hexachloride are of equal molar concentrations.

[0051] Comparative Example 5 (NWCS@CIS@CP)

[0052] The difference between Comparative Example 5 and Example 1 is that in step S31, the preparation method of solution B is: dissolving cobalt nitrate, nickel nitrate and tungsten hexachloride as cation sources in ethanol, wherein the cobalt nitrate, nickel nitrate and tungsten hexachloride are of equal molar concentrations.

[0053] Comparative Example 6 (FNWCS@CIS@CP)

[0054] The difference between Comparative Example 6 and Example 1 is that in step S31, the preparation method of solution B is: dissolving cobalt nitrate, nickel nitrate, iron nitrate and tungsten hexachloride as cation sources in ethanol, wherein cobalt nitrate, nickel nitrate, iron nitrate and tungsten hexachloride are equal in molar concentration.

[0055] Effect Example

[0056] The morphology and structure of the products prepared in Example 1 and Comparative Examples 1-2 were analyzed by scanning electron microscopy. Figure 1 (bd) are FE-SEM images of different samples. Figure 1 (b) is the FE-SEM image of the product obtained in Comparative Example 1; Figure 1 (c) is the FE-SEM image of the CIS@CP electrode prepared in Comparative Example 2, and the inset is a local enlarged image thereof; Figure 1 (d) is the FE-SEM image of the CFNWCS@CIS@CP electrode prepared in Example 1, and the inset is a local enlarged image; Figure 1 (el) is Figure 1 (d) The EDX mapping image inset. Figure 1 As shown in (ac), a vertical CIS nanosheet array structure was grown on the surface of a copper sheet by thermal sulfurization, and then CFNWCS high-entropy sulfide nanoparticles were deposited on the CIS nanosheets by SILAR process. Figure 1 (d) The inset image was subjected to EDX characterization. The results ( Figure 1 (el)) confirmed that Cd, Fe, Ni, W, Cu and S elements are uniformly distributed in CFNWCS high-entropy sulfides.

[0057] The crystal structures of the products in Example 1 and Comparative Example 2 were analyzed by powder X-ray diffraction (XRD) spectra. Figure 2The XRD patterns of different electrodes prepared in Comparative Example 2 and Example 1 are as follows: (a) is a spectrum with a 2θ range of 10-80°, and (b) is an enlarged spectrum with a 2θ range of 22.5-42.5° and 52-65°. The XRD results show that the samples of Comparative Example 2 and Example 1 both have characteristic peaks of the CIS crystal form, and the characteristic peaks of the CoS2 phase are also detected in the sample of Example 1, confirming that the high entropy sulfide CFNWCS may exist in the CoS2 crystal form. Further XPS analysis ( Figure 3 ) discloses in detail the elements contained in the sample of Example 1, with Cu + / Cu 2+ 、In 3+ , S 2- 、Co 2+ / Co 3+ , W 6+ 、Ni 2+ / Ni 3+ , Fe 3+ / Fe 2+ and Cd 2+ The coexistence of equivalent states further verifies the successful introduction of high-entropy sulfides.

[0058] In order to evaluate the HER performance of the photo-assisted electrocatalytic EOR coupled with the CFNWCS@CIS@CP electrode under full-spectrum simulated sunlight irradiation, the products obtained in Example 1 and Comparative Examples 1-6 were subjected to LSV tests ( Figure 4 (ab)). The results show that all samples obtained lower HER overpotentials under light conditions compared to the dark state, confirming that the photoactivity of the CIS substrate helps to enhance the photo-assisted electrocatalytic performance of the electrode ( Figure 4 (c)). In addition, with the increase of the number of cationic species in the surface-modified sulfide, the HER electrocatalytic performance of the electrode gradually improved, among which the CFNWCS@CIS@CP electrode in Example 1 had the best performance, which was due to the high entropy effect brought by the CFNWCS nanoparticles.

[0059] Different electrochemical tests were carried out in the photo-assisted electrocatalytic EOR coupled HER reaction system using the electrode prepared in Example 1. The results are as follows Figure 5-6 As shown, Figure 5 As shown in (a), the current density of the CFNWCS@CIS@CP electrode is between -10 and -100 mA / cm 2 When the overpotential changes within a certain range, the overpotential shows a rapid step response and when the current density drops back to -10 mA / cm 2When the overpotential is increased, the overpotential can be immediately restored to the initial state, indicating that the electrode has excellent interfacial charge transfer characteristics. At the same time, under light conditions, although the current density increases, it still shows the same rapid response trend, which means that the photogenerated charge can also be quickly transferred on the interface. Constant potential it test results ( Figure 5 (b) shows that the CFNWCS@CIS@CP electrode maintains good stability within 60 min during the photo-assisted electrocatalytic HER process. FE-SEM ( Figure 5 (b))、XRD( Figure 5 (c)) and XPS analysis ( Figure 6 ) also confirmed that its microscopic morphology, crystal structure and surface chemical composition did not change significantly. The H2 production during the constant potential test measured by gas chromatography was further compared with its theoretical calculated value, such as Figure 5 As shown in (d), the calculated Faradaic efficiency of the CFNWCS@CIS@CP electrode is above 80%.

[0060] The light absorption capacity of the products obtained in Example 1 and Comparative Examples 2-6 was analyzed by diffuse reflectance spectroscopy (DRS), and the diffuse reflectance spectra of different CIS@CP modified electrodes were compared ( Figure 7 (a)), CFNWCS high entropy sulfide modification significantly enhances the light absorption of the electrode in the 300-1500nm band, which is better than other non-high entropy sulfide modifications. The charge transport of the products in Example 1 and Comparative Examples 1-2 was studied by electrochemical impedance spectroscopy (EIS). Figure 7 (b), Table 1) further revealed that the introduction of high entropy sulfide in CFNWCS significantly reduced the charge transfer impedance at the electrode-solution interface, promoted the rapid transfer of electrons to the reaction species, and thus improved the electrocatalytic HER performance. It is worth noting that Figure 7 In (b), the semicircular arc radius in the EIS graph of the sample obtained in Example 1 under illumination conditions is smaller, and the interface charge transfer impedance is further reduced, reflecting the effective separation and rapid transfer of photogenerated carriers, which is beneficial to the improvement of the light-assisted electrocatalytic HER performance.

[0061] Table 1 is composed of Figure 7 (b) Fitting equivalent circuit parameter results

[0062] It should be noted that in Table 1, (-D) represents the test results of the samples in a dark state, and (-L) represents the test results of the samples under light.

[0063] Figure 8(ac) are dark state cyclic voltammetry (CV) test results of different electrodes prepared in Example 1 and Comparative Examples 1-2, (d) is a CV test result of CFNWCS@CIS@CP electrode sample under light, and the test potential range is the non-Faraday potential range. Figure 8 The CV test results of different electrodes in the non-Faraday potential range in the dark state shown in FIG. 1 can directly obtain the electrode-electrolyte solution double layer capacitance from the linear fitting slope, such as Fig. 9 As shown, it is proportional to the electrochemically active surface area (ECSA) of the electrode under test. As can be seen from the figure, the deposition of high-entropy sulfide CFNWCS nanoparticles can significantly increase the ECSA of the CIS@CP electrode, indicating that the number of HER reaction active sites on its surface increases, which is beneficial to reduce the energy barrier of the HER reaction and accelerate the reaction kinetics. Moreover, under light conditions, the ECSA of the CFNWCS@CIS@CP electrode increased by more than 2 times compared with the dark state. This shows that the light-assisted effect is one of the important reasons for promoting the improvement of the HER electrocatalytic performance of the electrode. Its mechanism can be attributed to the excellent full-spectrum response characteristics of the high-entropy sulfide CFNWCS, which can effectively excite the electrode surface to generate more high-energy photogenerated charges, thereby forming a light-assisted enhanced electrode surface activity.

[0064] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high entropy sulfide modified electrode material, It is characterized in that The main steps are as follows: S1, pre-treating the copper sheet; S2. Preparation of CIS@CP Electrode S21, dissolving anhydrous indium chloride and thioacetamide in the first solvent, adding glacial acetic acid, and continuously stirring to obtain a colorless and transparent solution A; S22, immerse the copper sheet pretreated in step S1 vertically into solution A and react at 80°C. After the reaction is completed, rinse the copper sheet with deionized water and dry it at room temperature, so that CuInS is in situ grown on the surface of the copper sheet. 2 Nanosheet arrays were formed to obtain CIS@CP electrodes; S3. Preparation of high entropy sulfide modified electrode materials using SILAR method S31, containing Co 2+ , W 6+ 、Ni 2+ , Fe 3+ , Cu 2+ The metal salt of the ion is dissolved in the second solvent as a cation source to obtain a solution B, and the sulfide is dissolved in the second solvent to obtain a solution containing S 2− ion solution C, and two portions of the second solvent are recorded as solution D and solution E; S32, placing the CIS@CP electrode obtained in step S2 in solution B, solution D, solution C and solution E in order and soaking each for 20 s, thus completing one soaking process; S33. Repeat step S32 several times, then wash, and then dry at 100°C for 2 hours, that is, CFNWCS nanoparticles are loaded on the CIS@CP electrode to obtain a high-entropy sulfide-modified electrode material, which is recorded as CFNWCS@CIS@CP electrode material.

2. A method for preparing a high entropy sulfide modified electrode material according to claim 1, It is characterized in that In step S1, the copper sheet is pretreated by successively using 400-mesh, 1000-mesh and 2000-mesh metallographic sandpaper to polish the surface of the copper sheet until it is smooth, then washing it, drying it at room temperature and storing it in anhydrous ethanol for later use.

3. The method for preparing a high entropy sulfide modified electrode material according to claim 1, It is characterized in that In step S21, the first solvent is deionized water; in step S31, the second solvent is ethanol.

4. The method for preparing a high entropy sulfide modified electrode material according to claim 1, It is characterized in that In step S21, the concentration of anhydrous indium chloride is 0.06 M, and the concentration of thioacetamide is 0.12 M.

5. The method for preparing a high entropy sulfide modified electrode material according to claim 1, It is characterized in that In step S21, the amount of glacial acetic acid added per milliliter of the first solvent is 12 μL.

6. The method for preparing a high entropy sulfide modified electrode material according to claim 1, It is characterized in that In step S31, Co 2+ , W 6+ 、Ni 2+ , Fe 3+ , Cu 2+ The metal salts of ions are cobalt nitrate, tungsten hexachloride, nickel nitrate, iron nitrate, and copper nitrate; the sulfide is Na 2 S.

7. The method for preparing a high entropy sulfide modified electrode material according to claim 1, It is characterized in that In step S31, the ions in the cation source of solution B have equal molar concentrations; The total molar concentration of the cation source in solution B is proportional to the S in solution C. 2- The molar concentration of the ions is equal, both are 50 mM.

8. The method for preparing a high entropy sulfide modified electrode material according to claim 1, It is characterized in that In step S33, step S32 is repeated 5 to 20 times.

9. A high entropy sulfide modified electrode material, It is characterized in that The method is prepared by the method described in any one of claims 1 to 8.

10. Use of the high entropy sulfide modified electrode material prepared according to claims 1 to 8 or the high entropy sulfide electrode material according to claim 9 in the field of hydrogen production by water electrolysis.